2015
DOI: 10.2214/ajr.14.13930
|View full text |Cite
|
Sign up to set email alerts
|

DWI for Renal Mass Characterization: Systematic Review and Meta-Analysis of Diagnostic Test Performance

Abstract: Evidence suggests moderate accuracy of DWI for the prediction of malignancy and high-grade clear cell cancers, whereas DWI performance for ascertaining clear cell histologic grade remains unclear. To develop DWI as a noninvasive approach for the evaluation of solid renal masses, prospective studies with standardized test parameters are needed to better establish DWI performance and its impact on patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Second, DWI was not used as it was not consistently acquired in all cases. Although there is no strong evidence for the use of DWI in the differentiation of histological subtypes of RCC (25), DWI may be used as an ancillary input to differentiate among some renal masses (26). Third, although conclusions on the diagnostic performance could have been influenced by the lack of strict adherence to the algorithm, our results suggest that accuracy was indeed higher when reviewers complied with the algorithm versus those instances when it was overruled; therefore, a trend caused by such factor would likely result in underestimation rather than overestimation of the algorithm performance.…”
Section: Discussionmentioning
confidence: 99%
“…Second, DWI was not used as it was not consistently acquired in all cases. Although there is no strong evidence for the use of DWI in the differentiation of histological subtypes of RCC (25), DWI may be used as an ancillary input to differentiate among some renal masses (26). Third, although conclusions on the diagnostic performance could have been influenced by the lack of strict adherence to the algorithm, our results suggest that accuracy was indeed higher when reviewers complied with the algorithm versus those instances when it was overruled; therefore, a trend caused by such factor would likely result in underestimation rather than overestimation of the algorithm performance.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis by Kang et al of diffusion-weighted imaging (DWI) studies in the characterization of renal masses showed moderate accuracy for distinguishing between benign vs. malignant lesions (86% sensitivity and 78% specificity) and low- vs. high-grade ccRCC (AUC of 0.83) (21). They found insufficient evidence, however, for discrimination of ccRCC from other histologies.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…Some investigators have reported some value in the determination of the histologic diagnosis in renal masses 35,36 and the characterization of high-grade RCC 37 . However, a recent meta-analysis indicated only moderate diagnostic accuracy in the characterization of renal masses and determination of high-grade clear cell histology 38 . The lack of standardization of the DWI acquisition protocols across different MRI vendors and different medical centers is likely responsible, at least in part, for the less than optimal diagnostic performance.…”
Section: Imaging Of Renal Cell Carcinomamentioning
confidence: 99%